Sustainable development model for nautical tourism ports - Jugovich, Alen; Kovacic, Mirjana; Hadzic, Ana (Tourism and hospitality management, 2011)
Nautical tourism ports make an open, dynamic and complex system which has been rapidly evolving; this is the reason why the development of this system requires continual monitoring and research. The existing models and development plans concerning nautical tourism ports donot provide for a systematic qualitative and quantitative development of nautical tourism, thus contributing to economical inefficiency likely to cause even ecological imbalance. The more so if nautical ports are regarded as business subjects by whom the concept of sustainable development is declaratively acceptable. For this reason, this paper presents in a systematic and clear way the results of the research based on an overall analysis and evaluation of nautical tourism ports’ position and development plans. On the basis of the results obtained, the paper presents a model of sustainable development of nautical tourism ports whereby the authors propose to redefine the approach to planning the development of nautical tourism and particularly to creating the offer and to understanding the relationship between economic development and environmental protection.